CARTESIAN PERSONAL METAPHYSICS - A. M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. To consider the personal nature of Cartesian metaphysics. Its implementation involves: a) outlining methodological changes in the philosophy of the twentieth century; b) analysis of ways to interpret anthropological component of philosophizing in Descartes studies; c) appeal to Descartes’ texts to clarify the authentic form of his interpretation of metaphysics. Theoretical basis. I base my view of Descartes’ legacy on the conceptual positions of phenomenology, existentialism and hermeneutics. Originality. Based on Descartes’ own concept of teaching, the author substantiates the personal nature of Cartesian metaphysics. Important prerequisites for its comprehension are attention to the ethical motive as the driving force of philosophizing and recognition of the importance of the poetic worldview. The idea of the basic role of poetics finds its meaningful confirmation in the texts of the philosopher, who interprets the main areas of philosophy (science, morality and medicine) as the forms of art. Conclusions. Based on his own vision of anthropology and metaphysics as the forms of completion of the revolution initiated by Copernicus, the author defends the idea of the constitutive presence of personality in Descartes’ metaphysics. In the process of studying the research literature, methodological guidelines are outlined in the form of the importance of personal determination of the search for truth, the key role of ethical motive and art as components of philosophizing. The thesis about the poetic form of presentation of metaphysics by Descartes as a form of fixation of its personal dimension is substantiated.